2016
DOI: 10.1007/s40891-016-0076-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a Nailed Soil Slope Using Limit Equilibrium and Finite Element Methods

Abstract: This paper aims at the two most common methods used for slope stability analysis. An attempt has been made to bring out the differences in results of reinforced slope stability analysis obtained from SLOPE/W (limit equilibrium based) and PLAXIS 2D (finite element based). The analysis is carried out on two slope angles of 45°and 60°, which are reinforced with nails at three different inclinations of 0°, 15°and 30°respectively. Both the slope angles and all nail inclinations are taken from the horizontal. A comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(24 citation statements)
references
References 37 publications
3
21
0
Order By: Relevance
“…FS resulted from limit equilibrium method tends to be larger than FS from finite element method. However, Rawat and Gupta [20] had reached a conclusion that the most stable slope from both analyses is found on the reinforced slope nail inclination. Park et al [21] implemented Bishop Simplified Method [15] in studying the reduction of slope stability due to the Gyeongju 5.8 ML Earthquake.…”
Section: Slope Stability Analysismentioning
confidence: 94%
See 1 more Smart Citation
“…FS resulted from limit equilibrium method tends to be larger than FS from finite element method. However, Rawat and Gupta [20] had reached a conclusion that the most stable slope from both analyses is found on the reinforced slope nail inclination. Park et al [21] implemented Bishop Simplified Method [15] in studying the reduction of slope stability due to the Gyeongju 5.8 ML Earthquake.…”
Section: Slope Stability Analysismentioning
confidence: 94%
“…The prediction yielded by finite element method is generally consistent with the field evidence. Rawat and Gupta [20] implemented both methods to observe the performance of nailed installed as slope reinforcement. FS resulted from limit equilibrium method tends to be larger than FS from finite element method.…”
Section: Slope Stability Analysismentioning
confidence: 99%
“…In numerical modeling, the shape of both geogrid and plate structural elements is rectangular with a width equal to 1 m in the perpendicular plane direction. Since the soil nail has a circular shape in cross-sectional area and nail heads are discrete square plates placed at designed horizontal spacing, it is required to determine equivalent axial and bending stiffness as circular for soil nails and square size for nail heads [19].…”
Section: Modelingmentioning
confidence: 99%
“…For the analysis of slope stability with soil nails, the shear strength reduction method can be adopted in FEM to estimate the factor of safety. The numerical analysis for soil nail structure by using FEM or FDM has been studied by numerous researchers [7,16,19,21,22,26]. These studies reported that increasing nail inclination could decrease the maximum tensile force in each nail, and the nail head could prevent local failure between nails.…”
mentioning
confidence: 99%
“…The main advantage of FEM is providing information about deformations of the soil nail system (Johari et al2020). Zhang et al (1999) developed a three-dimensional (3D) finite element model (FEM) for the deformation analysis of nailed soil structures; Babu et al (2007) analyzed a real vertical cut supported with retaining wall and soil nailing system, by 2D FEM program; Rawat and Gupta (2016b) analyzed using finite element software PLAXIS 3D the failure pattern and load-settlement plots for the various unreinforced and reinforced slopes. With the recent advances, the validation of soil nail models can be done using finite element software packages like Plaxis, Flac, GEO5, and Abaqus.…”
Section: Introductionmentioning
confidence: 99%